Exploring education for digital librarians meaning, modes and models - Myburgh, Sue; Tammaro, Anna Maria (Chandos information professional series, 2013)
"Exploring Education for Digital Librarians provides a refreshing perspective on the discipline and profession of Library and Information Science (LIS), with a focus on preparing students for careers as librarians who can deal with present and future digital information environments"--Back cover.